High-performance self-powered photodetectors achieved through the pyro-phototronic effect in Si/SnOx/ZnO heterojunctions - Silva, José Pedro Basto (2021)
Coupling together the pyroelectric effect and the photovoltaic effect is a novel method to significantly enhance the performance of photodetectors. In this work, we make use of this effect through a tri-layered heterojunction of n-Si/p-SnOx/n-ZnO, which takes advantage of the pyroelectric properties of the n-type ZnO film and the photovoltaic response of the n-type Si/p-type SnOx heterojunction. The photo-response of the device, with excitation from a 405 nm wavelength laser, is carefully investigated, and it is shown that the photodetector performance is improved with increased chopper frequency owing to the coupled photovoltaic-pyroelectric ef fect. The Al/Si/SnOx/ZnO/ITO device exhibits an optimum responsivity and detectivity of 36.7 mA/W and 1.5 × 1011 Jones, respectively, with a laser power density of 36 mW/cm2 and at a chopper frequency of 400 Hz. Ul trafast rise and fall times of 3 and 2 µs, respectively, were obtained. Moreover, by using a 650 nm wavelength laser source, the responsivity and detectivity were improved up to 64.1 mA/W and 2.4 × 1011 Jones, respec tively. The performance of these photodetectors is approximately twice as fast as other pyro-phototronic devices, and exhibits comparable photodetector characteristics when compared to perovskite/Si heterojunction and transition metal dichalcogenides lateral heterojunction devices. Therefore, by combining a pyroelectric ZnO film with a solar cell into one single structure, photodetectors based on the pyro-phototronic effect have been developed that demonstrate state-of-the-art performance. The devices show great promise for visible ultrafast photosensing.